The effect of serum levetiracetam concentrations on therapeutic response and IL1-beta concentration in patients with epilepsy - ONAT, FİLİZ; GÜLÇEBİ İDRİZ OĞLU, MEDİNE (ELSEVIER SCIENCE BV, 2018)
Objective: Assessment of the relevance between serum drug concentration to its therapeutic response is a valid monitoring strategy for the clinical efficacy of antiepileptic drugs (AEDs). Levetiracetam (LEV) is a broad spectrum AED with a possible anti-inflammatory effect. We aimed to determine the relationship between LEV concentrations and its therapeutic response, and the effect of LEV on IL1-beta concentrations in patients with epilepsy. Methods: Patients on monotherapy (n = 7) or polytherapy (n = 15) with LEV for their seizures management were included. Blood samples of each patient were collected: just before LEV intake, 1 h, 2 h, 4 h and 8 h following the last dose. Serum LEV concentrations were measured by liquid chromatography mass spectrometry and IL1-beta concentrations by chemiluminescent immunometric assay. Concentration to dose (C/D) ratio values was used for analyses. LEV concentrations were compared between responders (<= 1 seizure/month) and non responders (> 1 seizure/month) and patients with or without adverse reactions. IL1-beta concentrations before and at 2 h following LEV ingestion were compared in order to detect the effect of the increase in serum LEV concentration on IL1-beta. Results: Although there was no change in LEV (C/D) ratio or LEV maximum concentration (Cmax)/D ratio of the responders and non-responders, the C/D ratio following 1 h of LEV intake (2.17 +/- 0.59 kg.day/L) and Cmax/D ratio (2.25 +/- 0.56 kg.day/L) in the patients with adverse effects was significantly higher than for the patients without adverse effects (1.09 +/- 0.12 kg.day/L and 1.49 +/- 0.14 kg.day/L respectively). A statistically significant decrease was found in the IL1-beta concentration to LEV (C/D) ratio with the increase in LEV concentration in patients on LEV monotherapy. Conclusion: The possible relationship between LEV Cmax and its therapeutic response or IL1-beta concentrations may be an importance indication of LEV antiepileptic efficacy. Consequently, monitoring LEV Cmax values may enhance LEV adherence because patients would be less likely to develop adverse effects.
Keywords: Antiepileptic drugs; Seizure frequency; Adverse effect; Cytokine; ANTIEPILEPTIC DRUGS; ILAE-COMMISSION; CHILDREN; LAMOTRIGINE; EFFICACY